LINGO‐1 antibody ameliorates myelin impairment and spatial memory deficits in the early stage of 5XFAD mice. (9th February 2018) - Wu, Di; Tang, Xiang; Gu, Li‐Hua; Li, Xiao‐Li; Qi, Xin‐Yang; Bai, Feng; Chen, Xiao‐Chun; Wang, Jian‐Zhi; Ren, Qing‐Guo; Zhang, Zhi‐Jun
Summary: Aims: Multiple evidence has indicated that myelin injury is common in Alzheimer's disease (AD). However, whether myelin injury is an early event in AD and the relationship between it and cognitive function is still elusive. Methods: Spatial memory of 5XFAD mice was determined by Morris water maze at 1 and 3 months old. Meanwhile, the deposition of Aβ, the expression of myelin basic protein (MBP), LINGO‐1, NgR, and myelin ultrastructure in many memory‐associated brain regions were detected in one‐month‐old and three‐month‐old mice (before and after LINGO‐1 antibody administration) using immunostaining, Western blot (WB), and transmission electron microscopy (TEM), respectively. Results: No abnormal Aβ deposition was found in one‐month‐old 5XFAD mice. However, spatial memory deficits were proved in accordance with an obvious demyelination in memory‐associated brain regions in one‐month‐old mice and both deteriorated with age. Administration of LINGO‐1 antibody could obviously restore the myelin impairments in CA1 and DG region and partially ameliorate spatial memory deficits. Conclusions: Our results demonstrated that myelin injury was an early event in 5XFAD mice even prior to emergence of deposition of Aβ. Intervention with the LINGO‐1 antibody could attenuate impaired spatial memory deficits by remyelination, which suggested that myelin injury was involved in spatial memory deficits and remyelination may be a potential therapeutic strategy in early stage of AD or mild cognitive impairments.